Optimalisasi Pelayanan Publik di Kementerian Agama: Peran Strategis Analisis Kebutuhan Pelatihan (TNA) dalam Pengembangan Kompetensi Pegawai - Hamdi (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This Policy Paper analyzes the strategic role of training needs analysis (TNA) in optimizing public services within the Ministry of Religious Affairs through employee competency development. The quality of public services is often affected by the gap between employee competencies and job demands and public expectations. Therefore, TNA serves as a systematic method for identifying these gaps, thereby ensuring more targeted, efficient, and effective training programs. This study uses a qualitative method with a descriptive-analytical approach, reviewing various literature, internal documents, and relevant best practices to develop an adaptive TNA conceptual framework within the Ministry of Religious Affairs. The analysis shows that comprehensive TNA implementation, from problem identification and data collection from various sources (management, employees, and service users), to data analysis and the formulation of training recommendations, can significantly increase the relevance and positive impact of human resource development programs. TNA helps shift the approach to training from simply